The Trump Paradox: How Cues from a Disliked Source Foster Resistance to Persuasion - Nai, Alessandro (2020)
We usually reject information from sources we dislike. But what if those same sources explicitly disagree with that information? Are we more likely to be persuaded by information that is opposed by someone we dislike? We present results from an experimental study with a convenience sample of 199 Dutch students. Respondents were exposed to counter-attitudinal information on climate change in an attempt to generate persuasion, and in a second time exposed to a tweet from the current US president, Donald J. Trump, as a positive or negative endorsement of the counter-attitudinal. Results show that positive endorsements reduce the persuasive power of counter-attitudinal information, whereas negative endorsements (marginally) increase its persuasive power. These results have important implications in today’s politics, where “disliked” figures—most of the time referred to as “populists”—play an increasingly central role in framing the terms of the debate on the most salient issues.